28 June in the Serbian calendar of 1985–1991 - Yevgeni A. Koloskov (Центральноевропейские исследования, 2022)
The article is devoted to the formation of the contemporary Vidovdan tradition in the Socialist Republic of Serbia in 1985-1991. Beings the key date in modern Serbian national history, 28 June was used to provide commemorative practices by various Serbian forces during the decomposition of centralised power in Yugoslavia in that period. The process of codifying of a new national mythology precipitated by the disintegration processes in the SFRY after the death of Tito, is examined on the background of the political discourse in Serbia. The research uses sources such as the public speeches and writings of leading political figures (above all Slobodan Milosevic), which are openly available, for example the Memorandum of the Serbian Academy of Sciences and Arts, and which were published in the three most popular newspapers in the Socialist Republic of Serbia: Борба(Struggle), Политика (Politics) and Вечерње новости (Evening News) and the two main newspapers of the Autonomous Province of Kosovo: Rilindja (Revival) and Jeдинство (Unity). The research concludes that it is obvious that the establishing of a tradition of celebrating the anniversary of the Kosovo Battle as an annual public holiday is directly related to the interests of the political forces in SR Serbia.